Relationship of Acceptor Characteristics of Family Planning Implants with Sexual Disfunction in Gunung Sugih District, Central Lampung District in 2012 - Retno, Sri Nowo (KnE Life Sciences, 2019)
Sexual dysfunction is the inability to fully enjoy sexual intercourse. In Bandar Lampung, the case of sexual dysfunction in women reached 66.2%. This relates to the characteristics of sexual dysfunction of family planning acceptors implants that are age, education, work, the sheer number of children, BMI, and the duration of marriage. This study aims to determine the relationship of family planning acceptors characteristics with sexual dysfunction in the District of Central Lampung regency Mount Sugih 2012. This quantitative research was conducted on a sample of 178 respondents. Data were collected through interviews, data analysis was done using univariate, bivariate, and multivariate chi-square test and multivariate analysis odds ratios and logistic regression to determine the largest independent variables associated with sexual dysfunction. The results showed that the association of age with sexual dysfunction was p = 0.922, OR = 1.159, 95% CI 0.479 to 2.804; education , p = 0.000, OR = 4.141, 95% CI 2.055 to 8.346; work , p = 0.018, OR = 2.316, 95% CI 1.197 to 4.484; number of children , p = 0.034, OR = 0.316, 95% CI 0.115 to 0.868; IMT , p = 0.491, OR = 0.678, 95% CI 0.292 to 1.571; and long marriage , p = 0.031, OR = 0.336, 95% CI 0.131- 0.860. The study showed that there is no relationship between age and BMI and the relationships between education, occupation, number of children, and duration of marriage. To reduce the incidence of sexual dysfunction in family planning acceptors, there is a need for increased promotional efforts, counseling, informed consent and informed choice, and providing counseling on sex, family planning, and the possible side effects from the use of contraceptive devices and finally setting up sexual consultation clinics.